Greece : Preliminary Draft Debt Sustainability Analysis. (IMF Staff Country Reports; Country Report, 2015)
This paper analyzes the debt sustainability in Greece. At the last review in May 2014, Greece's public debt was assessed to be getting back on a path toward sustainability, though it remained highly vulnerable to shocks. By late summer 2014, with interest rates having declined further, it appeared that no further debt relief would have been needed under the November 2012 framework, if the program were to have been implemented as agreed. But significant changes in policies since then are leading to substantial new financing needs. To ensure that debt is sustainable with high probability, Greek policies will need to come back on track.